Acclimatization of anaerobic sludge with cow manure and realization of high-rate food waste digestion for biogas production. (November 2020) - Xing, Bao-Shan; Han, Yule; Wang, Xiaochang C.; Cao, Sifan; Wen, Junwei; Zhang, Kaidi
Graphical abstract: Highlights: Long-term acclimatization of anaerobic sludge was conducted with cow manure (CM). Acclimated sludge showed stable microbial community and enzyme activity. High-rate FW digestion and CH4 production was achieved without continued CM addition. Maximum CH4 production was as high as 5.86 L/L/d with OLR = 16.8 g COD/L/d. Continued enrichment of functional bacteria contributed to high-rate FW digestion. Abstract: Long-term acclimatization of anaerobic sludge was conducted by operating a mesophilic continuously stirred anaerobic reactor (CSTR) with continuous feeding of food wastes (FW) and cow manure (CM). During the long-term acclimatization, continued increase of enzyme activity was revealed, while the microbial structure tended stable as shown by the Shannon index and microbial community. By biomethane potential analysis, the acclimated sludge had a methane yield about 13 times higher than the initial anaerobic sludge. The acclimated sludge was subsequently used for FW digestion with stepwise organic loading rate increase without CM addition. The functional phyla of Bacteroidetes and Proteobacteria, which originated from CM but not very abundant, were significantly enriched not only during sludge acclimatization with CM addition but also in the process of FW digestion without CM addition. A microbe coexistence network was proposed to support an explanation of the metabolic pathways of FW digestion using the acclimated sludge.